2014
DOI: 10.4238/2014.january.31.2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of key genes of unruptured intracranial aneurysms by using DNA microarray data analysis techniques

Abstract: ABSTRACT. This study aimed to identify differentially expressed genes (DEGs) of unruptured intracranial aneurysms (IAs) and provide beneficial information for early diagnosis and treatment of IAs. The gene expression profile GSE26969 from the Gene Expression Omnibus database was downloaded, which included six human IA samples: three intracranial arterial aneurysm samples and three normal superficial temporal artery samples (control). Based on these data, we identified the DEGs between normal and disease sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although no significant vascular abnormality has been evidenced in the patient reported here, nor in her brother, it remains a possibility, as MYL9 expression has been demonstrated in vascular smooth muscle [26,27]. Additional studies are necessary to define a possible vascular manifestation in MMIHS.…”
Section: Discussionmentioning
confidence: 69%
“…Although no significant vascular abnormality has been evidenced in the patient reported here, nor in her brother, it remains a possibility, as MYL9 expression has been demonstrated in vascular smooth muscle [26,27]. Additional studies are necessary to define a possible vascular manifestation in MMIHS.…”
Section: Discussionmentioning
confidence: 69%
“…In the label-free proteomic analysis, proteins that play a role in IA pathology were found, which mirrored the results found in previous studies using iTRAQ ( Wang et al, 2016 ). Using a DNA microarray, Chen et al (2014) found that myh11, acta2, mlck, and my19 were differentially expressed genes associated with VSMC contraction ( Chen et al, 2014 ). Our study focused on SMCs and highlighted the impact of losing MLCK on IA formation.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the development of bioinformatic tools appeared a new type of study presenting re-analyzed data from available datasets, including expression data from the Gene Expression Omnibus (GEO). Approximately one third of these published secondary analyses utilized a single dataset [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] and two thirds leveraged data from two to eight datasets [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. These studies did not provide any new additional clinical data but rather aimed to deepen the insight into molecular mechanisms of the IA pathophysiology by revealing key regulatory networks and interactions between investigated molecules.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%